Heritability of cough across two generations: the RHINESSA study - Össur Ingi Emilsson; Henrik Johansson; Ane Johannessen; Christer Janson; Andreas Palm; Karl A. Franklin; Anna Oudin; Francisco Gómez Real; Mathias Holm; Thorarinn Gislason; Eva Lindberg; Rain Jõgi; et al. (ERJ Open Research)
Aim Heritability of cough has not yet been studied. We aimed to evaluate if individuals with cough are more likely to have offspring who develop cough, and if these associations differ by type of cough (productive/nonproductive). Methods The RHINESSA Generation Study (Respiratory Health In Northern Europe, Spain and Australia) includes 7155 parents (initially aged 30–54) answering detailed questionnaires in 2000 and 2010, and 8176 offspring ≥20 years answering similar questionnaires in 2012–2019. Chronic cough was categorised as productive or nonproductive (dry) cough. Associations between parental and offspring cough were analysed using mixed-effects logistic regression, adjusting for offspring age, sex, body mass index, smoking history, education level, current asthma, rhinitis, nocturnal gastroesophageal reflux; parent sex and smoking history; centre and family. Results Among parents with nonproductive cough, 11% of their offspring reported nonproductive cough, compared with 7% of offspring to parents without nonproductive cough, adjusted odds ratio (aOR) 1.59 (95% confidence interval 1.20–2.10). Among parents with productive cough, 14% of their offspring reported productive cough, compared with 11% of offspring to parents without productive cough, aOR 1.34 (1.07–1.67). No associations were found between parent productive cough–offspring nonproductive cough, nor between parent nonproductive cough–offspring productive cough. Conclusions Parents with chronic cough are more likely to have offspring with chronic cough independent of parental asthma, suggesting cough to be a separate heritable trait. The type of cough is important, as the nonproductive cough in parent associates only with nonproductive cough in offspring, and the same applied for productive cough.